The Role of Brief Global Cognitive Tests and Neuropsychological Expertise in the Detection and Differential Diagnosis of Dementia - Riello, Marianna; Rusconi, Elena; Treccani, Barbara (Frontiers in Aging Neuroscience, 2021)
Dementia is a global public health problem and its impact is bound to increase in the next decades, with a rapidly aging world population. Dementia is by no means an obligatory outcome of aging, although its incidence increases exponentially in old age, and its onset may be insidious as a certain amount of non-pathological cognitive decline can be expected with aging. In the absence of unequivocal biomarkers, the accuracy of cognitive profiling plays a fundamental role in the diagnosis of this condition. Here we highlight the utility of brief global cognitive tests in this diagnostic process, from the initial detection stage for which they are designed, to the differential diagnosis of dementia. We also argue that neuropsychological training and expertise are critical in order for the information gathered from these omnibus cognitive tests to be used in an efficient and effective way, and thus, ultimately, for them to have such a utility .